Mobile Banking: Can Financial Services be Extended to Africa's Unbanked? - Tschiemer, Robert A. (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: Beginning with an analysis of financial access barriers and market opportunities, four commercial mobile banking business models are analyzed in order to find out what their potential is for creating inclusive financial markets across Sub-Saharan Africa. By applying a comparative case study research design, the models are assessed with respect to their business strategy, market strategy, and the enabling business environment. The result is that all models are able to extend financial services to the unbanked, yet only to a limited extent so far. Services are dominated by payments and deposits, while microfinance loans are yet to be implemented. Among a range of environmental variables that may affect the replicability of business models, the business regulatory environment and legal rights of borrowers and lenders appear to clearly be the most important factors, followed by trade, while demographic and socioeconomic factors were deemed not to be significant.